2021
DOI: 10.13189/ujaf.2021.090111
|View full text |Cite
|
Sign up to set email alerts
|

Do Intangible Assets and Innovation Orientation Influence Competitive Advantages? A Case Study of SMEs in Indonesia

Abstract: Competition in small and medium-sized businesses (SMEs) is growing in the era of transition. As a result, these advances are putting pressure on the retail sector to find new and efficient solutions to boost retail and customer experience. Meanwhile, in Central Java, Indonesia, there is one specific SME type that is part of the nation's cultural heritage, namely Batik SME. This study aims to determine the effect of Intangible Assets and Innovation Orientation on the Competitive Advantages of Batik SMEs in Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The findings provided by our research reaffirm, more broadly, that these companies use socially based market regulations to respond to the economic, social, education, health, workforce development and environmental problems faced by B companies. Social entrepreneurs generate impact from what others see as feasibility, such as employing the disabled to create a competitive advantage [114][115][116]. They challenge the prevailing assumption that profit firms incrementally and/or independently improve their practices to support the initially intended impact.…”
Section: Discussionmentioning
confidence: 99%
“…The findings provided by our research reaffirm, more broadly, that these companies use socially based market regulations to respond to the economic, social, education, health, workforce development and environmental problems faced by B companies. Social entrepreneurs generate impact from what others see as feasibility, such as employing the disabled to create a competitive advantage [114][115][116]. They challenge the prevailing assumption that profit firms incrementally and/or independently improve their practices to support the initially intended impact.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Porter [70] showed that competitive advantage refers to the marketplace's comparative positional leadership that enables a firm to outperform its competitors. Iriyanto et al [43] described competitive advantage as improved efficiency, improved quality, increased productivity, or cost reductions. Concurrently, Rothaermel [56] described competitive advantage as a firm's formulation and execution of a policy that leads to superior performance when compared to its competitors in the market.…”
Section: Finance-competitive Advantagementioning
confidence: 99%
“…However, in Figure 1 we also add to the role of open innovation and engagement theories to facilitate business in the craft industry. Open innovation is always required to ensure the industry competitive and profitable for all participants [8,21,43,44]. We have found that the implementation of open innovation can improve the business performance of a firm [48].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Moreover, market and technology dynamics are increasing every time. Indonesian batik SMEs must know their challenges and adopt open innovation to improve their performance and competitive advantage [8,9]. Yun et al [10] stated that open innovation has a definition where an organization relies not only on its technology to innovate but also on external knowledge and other technologies (such as user innovation, customer innovation, collective intelligence, crowdsourcing, etc.).…”
Section: Introductionmentioning
confidence: 99%